Colonial Africa in official statistics, 1821-1953. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2012)
These statistics cover the history of thirteen colonies across Africa. The date range of statistics for each colony depends on who ran it at the time. Most colonial statistics cover that colony's funds, its population and the names of its officers. Details of which countries each colony was trading with and what they bought or sold were recorded in these books. Public services which were run by the British colonies are also covered by these records. The statistics for Africa told the Colonial Office how the British Empire was performing as a business. Some topics in these books only appear in a few issues: population numbers for slaves would be recorded until the abolition of slavery. However, military spending would only be included at times of war. The imperial statistics in this collection are listed by year for ease of reference.
Date range: 1821-1953.
Keywords: Africa -- History -- 19th century; Africa -- History -- 20th century; Colonies -- Africa